An in vitro synthetic biology platform for the industrial biomanufacturing of myo‐inositol from starch. Issue 8 (8th May 2017) - You, Chun; Shi, Ting; Li, Yunjie; Han, Pingping; Zhou, Xigui; Zhang, Yi‐Heng Percival
ABSTRACT: Myo‐Inositol (vitamin B8) is widely used in the drug, cosmetic, and food & feed industries. Here, we present an in vitro non‐fermentative enzymatic pathway that converts starch to inositol in one vessel. This in vitro pathway is comprised of four enzymes that operate without ATP or NAD + supplementation. All enzyme BioBricks are carefully selected from hyperthermophilic microorganisms, that is, alpha‐glucan phosphorylase from Thermotoga maritima, phosphoglucomutase from Thermococcus kodakarensis, inositol 1‐phosphate synthase from Archaeoglobus fulgidus, and inositol monophosphatase from T. maritima . They were expressed efficiently in high‐density fermentation of Escherichia coli BL21(DE3) and easily purified by heat treatment. The four‐enzyme pathway supplemented with two other hyperthermophilic enzymes (i.e., 4‐α‐glucanotransferase from Thermococcus litoralis and isoamylase from Sulfolobus tokodaii ) converts branched or linear starch to inositol, accomplishing a very high product yield of 98.9 ± 1.8% wt./wt. This in vitro (aeration‐free) biomanufacturing has been successfully operated on 20, 000‐L reactors. Less costly inositol would be widely added in heath food, low‐end soft drink, and animal feed, and may be converted to other value‐added biochemicals (e.g., glucarate). This biochemical is the first product manufactured by the in vitro synthetic biology platform on an industrial scale. Biotechnol. Bioeng. 2017;114: 1855–1864. © 2017 Wiley Periodicals, Inc. Abstract : Myo‐Inositol (vitamin B8) is produced via an in vitro non‐fermentative enzymatic pathway that biotransforms starch to inositol. The pathway comprised of up to six carefully‐chosen hyperthermophilic enzymes in one vessel can work well without ATP or NAD + supplementation. The enzyme cocktail achieved a very high inositol yield of 99% wt/wt. This biochemical is the first product manufactured by the in vitro synthetic biology platform on an industrial scale (e.g., 20, 000‐L bioreactors).